Application of susceptible-infected-removed model with vital dynamics for COVID-19 outbreak in Malaysia / Teoh Yeong Kin ... [ et al.] - Teoh, Yeong Kin; Hamdan, Nur Fatihah; Abu Hasan, Suzanawati; Ariffin, Anas Fathul; Mahat, Aishah (Universiti Teknologi MARA, Perlis, 2021)
In late 2019, the unique severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), also known as COVID-19, first emerged in Wuhan City, Hubei Province, China and quickly spread throughout the world. Until June 30, 2022, a total of 4,566,055 cases of COVID-19 have been reported in Malaysia, with 35,765 deaths and 4,500,856 recovered cases. This study aims to generalise a deterministic SIR model with vital dynamics for understanding the proliferation of infectious diseases. The SIR model with vital dynamics is more realistic in mimicking reality than the basic SIR model because it can determine the dynamic behaviours of COVID-19 over a more extended period. The SIR model utilises vital dynamics with unequal birth and death rates. Furthermore, the SIR model with vital dynamics is rescaled with the total time-varying population and analysed according to its epidemic condition. The results indicated that the number of infected individuals would peak about 10 - 15 days and reach their steady state about 25 - 60 days. The findings of this research may help policymakers establish, plan, and implement effective COVID-19 pandemic response strategies.